ANALYSIS OF WORD ORDER IN ARABIC WITHIN THE THEORY OF GENERALIZED PHRASE STRUCTURE GRAMMAR - MANSOUR, AYAD S. (Journal of Duhok University, 2017)
The aim of this work is to analyze word order variations of modern standard Arabic sentences within the linguistic framework of Generalized Phrase Structure Grammar (GPSG) by Gazdar, Pullum, Klein, and Sag (1985). This paper provides a direct interpretation as to the word order variations in Arabic either through a rule-to-rule formalism (including metarules in addition to other generalizations as for the rules of the grammar) or semantics. It tends not to suppose multistratal syntactic representations.